Metabolomics and transcriptomics analyses for characterizing the alkaloid metabolism of Chinese jujube and sour jujube fruits - Xue, Xiaofang; Zhao, Ailing; Wang, Yongkang; Ren, Haiyan; Su, Wanlong; Li, Yi; Shi, Meijuan; Liu, Li; Li, Dengke (Frontiers in Plant Science, 2023)
Jujube is an important economic forest tree whose fruit is rich in alkaloids. The mechanisms underlying the synthesis and metabolism of alkaloids in jujube fruits remain poorly understood. In this study, we first integrated widely targeted metabolomics and transcriptomics analyses to elucidate the metabolism of alkaloids in the fruits of Ziziphus jujuba ‘Hupingzao’ and Ziziphus spinosa ‘Taigusuanzao’, two important species of the jujube genus, at different harvest stages. In the metabolomics analysis, 44 alkaloid metabolites were identified in 4 samples, 3 of which were unique to sour jujube fruit. The differential alkaloid metabolites (DAMs) were more accumulated in sour jujube than in Chinese jujube; further, they were more accumulated in the white ripening stage than in the red stage. DAMs were annotated to 12 metabolic pathways. Additionally, transcriptomics data revealed 259 differentially expressed genes (DEGs) involved in alkaloid synthesis and metabolism. By mapping the regulatory networks of DAMs and DEGs, we screened out important metabolites and 11 candidate genes. Taken together, our results provide insights into the metabolic networks of alkaloid synthesis in Chinese jujube and sour jujube fruits at different harvest stages, thereby providing a theoretical reference for the development and utilization of jujube alkaloids.